Ideal Cardiovascular Health and Biomarkers of Subclinical Brain Aging: The Northern Manhattan Study. Issue 16 (21st August 2018) - Gardener, Hannah; Caunca, Michelle; Dong, Chuanhui; Cheung, Ying Kuen; Alperin, Noam; Rundek, Tatjana; Elkind, Mitchell S. V.; Wright, Clinton B.; Sacco, Ralph L.
Abstract : Background: The American Heart Association Life's Simple 7 metric defines ideal cardiovascular health (CVH) on 7 factors: smoking, diet, physical activity, body mass index, blood sugar, blood pressure, and cholesterol. This metric has been used to define optimal brain health, but data relative to subclinical imaging biomarkers of brain aging are lacking. This study examines the association between Life's Simple 7 with white matter hyperintensity volume, silent brain infarcts, and cerebral volume. Methods and Results: A subsample of stroke‐free participants from the population‐based Northern Manhattan Study underwent brain magnetic resonance imaging an average of 7 years after baseline. Linear and logistic regression models were constructed to estimate associations between the number of ideal CVH metrics achieved with imaging biomarkers of brain aging, adjusting for sociodemographics. Among 1031 participants (mean age at magnetic resonance imaging=72±8, 40% men, 19% black, 16% white, and 65% Hispanic), no one had ideal status in all 7 factors, 1% had ideal status in 6 factors, 18% in 4 to 5 factors, 30% in 3 factors, 33% in 2 factors, and 18% in 0 to 1 factors. The number of ideal CVH factors achieved was inversely associated with white matter hyperintensity volume (beta per factor=−0.047; P =0.04) and silent brain infarct (odds ratio per factor=0.84; 95% confidence interval=0.72–0.97) and positively associated with cerebral volume (beta per factor=0.300; P =0.002). Conclusions: An increasing ideal CVH score was associated with less white matter hyperintensity volume and silent brain infarcts and greater cerebral volumes, supporting the Life's Simple 7 metric as a useful measure to quantify optimal brain health. Monitoring and promoting achievement of Life's Simple 7 ideal CVH factors may improve subclinical and clinical brain health outcomes.